Photosynthetic heat tolerance in plants with different foliar water ‐uptake strategies - Boanares, Daniela; Lemos‐Filho, José P.; Isaias, Rosy M. S.; França, Marcel G. C. (American journal of botany, 2021)
Premise The distribution and even the survival of plant species are influenced by temperature. In an old climatically buffered infertile landscape (OCBIL) in Brazil, we previously characterized different strategies for foliar water uptake (FWU). It is possible that photosystem II tolerance to heat and excessive light intensity varies among species with different FWU capacities. Methods The relationship between FWU, photoinhibition, and thermotolerance was investigated in seven species from this ecosystem. Results The species with slow water absorption and high water absorption are those that presented less photoinhibition. Contrastingly, the species that have fast and low water absorption presented greater thermotolerance when their leaves are totally hydrated. However, when there is greater leaf dehydration, the most thermotolerant species were those with slow but high water absorption. Conclusions Foliar water uptake is an important trait for plants to tolerate excessive light intensity and higher temperatures. Plants in this OCBIL may be differentially affected by future global warming, and the best strategy to deal with this expected climate change is with slow and high absorption of water.